Method for particle ensembles control under uncertainty - Zadorozhny, V. (Вопросы атомной науки и техники, 2008)
The paper is devoted to the issues related to nonlinear dynamics of controlled intensive charged particle beams. Study the beams possessing exceptionally large inherent fields and extreme high impulse intensity and energy calls for new cybernetic approaches aimed to developing controlling algorithm of optimal behavior. We describe the beam distribution in particle accelerations (a Vlasov-Maxwell scheme) in the framework of differential games and control problem. This paper proposes an optimal approach for the well-known partial differential equation of Vlasov involving semi-group contraction and dissipative operators in Hilbert space. Статья посвящена нелинейной динамике управления интенсивными пучками заряженных частиц. Мы описываем распределение пучка при ускорении частиц (схема Власова-Максвелла) в системе дифференциальных игр и проблемы управления. Эта работа предлагает оптимальный подход для хорошо известного дифференциального уравнения Власова в частных производных, использующий полугрупповую контракцию и диссипативные операторы в гильбертовом пространстве. Стаття присвячена нелінійній динаміці керування інтенсивними пучками заряджених частинок. Ми описуємо розподіл пучка при прискоренні частинок (схема Власова-Максвелла) у системі диференційних ігор та проблеми керування. Ця робота пропонує оптимальний підхід для добре відомого диференційного рівняння Власова у частинних похідних, що застосовує напівгрупову контракцію та дисипативні оператори в гільбертовому просторі.